Fluorescence detection of aromatic amines and photocatalytic degradation of rhodamine B under UV light irradiation by luminescent metal–organic frameworks1. (2nd June 2015) - Wang, Fengqin; Dong, Caifu; Wang, Chengmiao; Yu, Zongchao; Guo, Shukun; Wang, Zechuan; Zhao, Yongnan; Li, Guodong
<x xml:space="preserve">Abstract</x> Two MOFs were employed as fluorescence materials for selectively sensing aromatic amines as well as the photodegradation of organic dyes.